Reading accuracy and naming speed in primary school children - González-Valenzuela, María José; Díaz-Giráldez, Félix; Delgado-Ríos, Myriam; Martín-Ruiz, Isaías (My University, 2014)
The aim of this study is to determine whether naming speed predicts word reading accuracy at the beginning of primary education. The sample consists of a group of 120 students of Elementary Education, 65 boys and 55 girls, between 6 and 7 years (M= 79.79 months; SD= 3.44). The accuracy in reading words and speed of naming colors, pictures, letters and numbers were evaluated. The results of the regression analysis shows that 13% of the variance in reading accuracy is explained by the speed of naming colors, images, numbers and letters. Naming speed is a good predictor of reading accuracy even at the beginning of compulsory education.
Keywords: Lectura; Enseñanza primaria; Reading accuracy; Naming speed; Primary school